Підходи до трактування поняття «розширена школа» - Вознюк, Віктоія (Studies in Comparative Education, 2014)
У статті розглянуто підходи до трактування досліджуваного поняття провідних теоретиків розширених шкіл і визначення, подані в нормативних актах розвинутих англомовних країн світу (Велика Британія, США, Австралія) та здійснено їх порівняльний аналіз. Визначено типи послуг, які надає розширена школа. З’ясовано сутність міжвідомчого партнерства та виокремлено релятивні до нього поняття. Проаналізовано сутність дитячих центрів впевненого старту (Sure Start Children’s Centers) як провідних партнерів розширених шкіл щодо забезпечення догляду за дітьми раннього віку. В статье рассмотрены подходы к трактовке исследуемого понятия ведущих теоретиков расширенных школ и определения, поданные в нормативных актах развитых англоязычных стран мира (Великобритания, США, Австралия) и проведен их сравнительный анализ. Определены типы услуг, которые предоставляет расширенная школа. Раскрыта сущность межведомственного партнерства и выделены релятивные к нему понятия. Проанализирована сущность детских центров уверенного старта (Sure Start Children’s Centers) в качестве ведущих партнеров расширенных школ по обеспечению ухода за детьми раннего возраста. The article describes the approaches to the interpretation of the concept by the leading theorists as well as definitions given in regulations of the developed English-speaking world (UK, USA, Australia). The comparative analysis of the definitions is conducted. The types of services that provide extended schools are defined. The essence of the inter-agency partnership and related to it concepts are analyzed. The essence of childcare in the Sure Start Children’s Centers as leading partners of the extended schools in the provision of care for young children is analyzed. Having reviewed the approaches to the interpretation of the concept of the extended school of various scholars and legislative acts, the author concluded that the extended school is a specific type of a school providing a broad range of services to consumers educational and social services and functions as the core of the community. After a more detailed analysis of the key elements and services specified type of the educational institution the letter was defined as advisable to disseminate British experience in the Ukrainian educational system.